Acute Recurrent Pancreatitis: A Possible Clinical Manifestation of Ampullary Cancer - Petrou, Athanasios; Bramis, Konstantinos; Williams, Timothy; Papalambros, Alexandros; Mantonakis, Eleftherios; Felekouras, Evangelos (JOP. Journal of the Pancreas, 2011)
<!--[if gte mso 9]> 72 544x376 <![endif]--><!--[if gte mso 9]> Normal 0 14 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Context Acute recurrent pancreatitis still poses diagnostic difficulties. The coexistence or moreover the causative relationship of carcinoma of the ampulla of Vater and acute recurrent pancreatitis is fairly rare. Case report We present a case of carcinoma of the ampulla of Vater that presented with acute recurrent necrotizing pancreatitis complicated with pseudocysts. A diagnosis of malignancy in the ampulla was only made after several ERCP attempts due to residual inflammation at the periampullary area. Conclusion Malignancy at the ampulla of Vater causing recurrent episodes of pancreatitis represents a realistic risk and attempts to diagnose the underlying cause should always take into account the possibility of cancer.